PROSPEK PENGEMBANGAN DAN STRATEGI PEMASARAN KOMODITAS KOPI ROBUSTA RAKYAT DI KABUPATEN JEMBER - Dimas Bastara; Martono Achmar (Program Studi Agribisnis Fakultas Pertanian, 2012)
Jember is the only area that has a research center of coffee and cocoa, therefore coffee products in Jember regency have the opportunity to develop. Coffee-producing area in Jember regency is also quite a lot, so that the coffee in Jember is fairly easy to dotain. Based on the data from the Department of Plantation East Java, Jember is known as the second largest people’s Robusta coffee cultivation after the regency of Malang in East Java. The marketing of Robusta coffee in Jember is confined to the area of ​​production only, though most production is marketed outside the region but in fact it is not maximized. This study aims at determining: (1) Prospect of Robusta coffee in Jember regency, (2) The Robusta coffee marketing strategy in Jember. This study uses primary data. The location of this research is determined intentionally (Purposive Method). The sampling method used in this study is Area Sampling or sample area. The sample measure’s are used Slovin’s formulation and then the samples are choiced by simple random sampling. The analysis tools used are the SWOT analysis (Strength, Weakness, Opportunity, Threat) and the descriptive methods.